Vertical Social Infrastructures: Redefining Community Interaction In High-Rise Urban Housing - Zuzana, Zuzana; Štrochová, Štrochová (University of Science and Computer Technology, 2025)
This study examines how graphic design functions as a social infrastructure within high-rise urban housing, shaping interactions, identity, and collective well-being. Urbanization has driven vertical expansion, creating new spatial and social challenges that affect community cohesion. While existing research in architecture and urban sociology has focused on spatial design and technological efficiency, this study highlights the overlooked role of visual communication as an active mediator of social relations. The research introduces the concept of Vertical Social Infrastructures, which reframes high-rise housing as a visual–social system rather than merely a physical structure. Using comparative analysis, the study explores how graphic elements, color, signage, murals, and typography can guide interaction and create shared narratives in dense residential settings. The study explicitly contributes to the field of graphic design by demonstrating how visual communication — including color, signage, murals, and typography — mediates social interaction and spatial behavior in vertical housing environments. This connection reinforces the journal’s focus on the intersections between design, media, and society, positioning graphic design as both an analytical and infrastructural framework for community engagement. The findings demonstrate that graphic design serves as a connective infrastructure, enhancing spatial legibility and fostering social engagement. By integrating theories from design studies, social infrastructure, and urban communication, this paper contributes a cross-disciplinary framework for understanding design as a medium of social sustainability. The results suggest that visual design strategies can transform vertical housing into inclusive, participatory, and emotionally resonant environments.